Beyond the solar system : exploring galaxies, black holes, alien planets, and more : a history with 21 activities - Carson, Mary Kay (Chicago Review Press, 2013)
Tracing the evolution of humankind's pursuit of astronomical knowledge, this resource looks deep into the furthest reaches of space. Children will follow along as the realization that the Earth is not at the center of the universe leads all the way up to recent telescopic proof of planets orbiting stars outside the solar system. In addition to its engaging history, this book contains 21 hands-on projects to further explore the subjects discussed. Readers will build a three-dimensional representation of the constellation Orion.